Georg Simmel’s Social Aesthetics and the Digital Public Sphere - Serafini, Luca (Simmel Studies)

(untitled) (Edizioni ETS, 2021)
In this paper I use concepts of Georg Simmel’s social aesthetics to investigate and describe several relational and communicative dynamics that occur in the digital public sphere—where the aesthetic dimension has now assumed great importance. Specifically, Simmel’s work proves to be more suited than Habermas’s for understanding the mechanisms of “typification” and “gamification” found in online interactions between individuals. I further argue that, on the Web, these mechanisms in particular are responsible for blocking the exchange of opinions and meanings on subjects of public interest, thereby betraying the universal, societal outcomes of Simmel’s social aesthetics.